Relationship between Sprint, lower limb power, and change of direction speed in adolescents - Júlio Brugnara Mello; Eraldo dos Santos Pinheiro; Gustavo Dias Ferreira; Gabriel Gustavo Bergmann (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: The purpose of this study is to verify the association between sprint, lower limb power, and change of direction speed in schoolchildren. Method: This is a cross-sectional school-based study with a probabilistic sample (n=1455) of adolescents aged 10-17 years. The variables were: sex, chronological age, body mass, height, skinfold sum, maturity offset, lower limb power, change of direction speed, and sprint. For the data analyses, we used a t-test for independent samples, Pearson correlation, and multiple linear regression. A statistical significance level of 5% was considered for all analyses. Results: The three variables of physical fitness presented moderate and significant correlations between them (r = {0.39-0.61}). Three models were tested with sprint (model 1), change of direction sprint (model 2) and lower limb power (model 3) as an outcome. Predictors tested explain 47% of model 1, 49% of model 2, and 54% of model 3. The individual predictor's contribution in both models varied between 0.1% to 38%. Conclusions: The evidence suggests that change of direction speed and sprint, together with sex, body mass, and skinfold sum account for approximately 54% of the variance of lower limb power in adolescents aged 10-17 years.